The Effect of Microwave Blanching as a Green Chemistry Technique on the Quality of Lotus Rhizome Slices - Akanksha S.; Vivek K. (My University, 2025)
Microwave radiation is a clean alternative to conventional energy and hence is used in green chemistry. Blanching is an effective pretreatment technique used to inactivate browning enzymes in vegetables. The effect of microwave blanching at 360 W, 540 W and 900 W was studied in comparison to hot water blanching at 90°C and 50°C and steam blanching on lotus rhizome slices. This vegetable crop was selected because it is an amalgamation of good taste, rich nutrient content and crisp texture. The time of all the blanching methods was optimized to minimize nutritional and quality losses. Blanching efficacy was checked by the inactivation of peroxidase and catalase enzymes. Several quality parameters, such as ascorbic acid content, hardness, residual activity of the enzymes peroxidase and polyphenol oxidase, browning index and microstructural analysis, were determined. An increase in ascorbic acid content was observed after microwave blanching. Similarly, texture and microstructure were also found to be intact in microwave-blanched lotus rhizome slices compared to steam- and hot-water-blanched samples. Higher nutritional loss was observed in the case of hot water blanching due to leaching, making it an inefficient method of blanching. Browning decreased under all three treatments equally. Microwave blanching can therefore be regarded as the best and most ecologically sustainable pretreatment method.